The biomedical application of inorganic metal nanoparticles in aging and aging-associated diseases - Yuqing Meng; Junzhe Zhang; Yanqing Liu; Yongping Zhu; Haining Lv; Fei Xia; Qiuyan Guo; Qianli Shi; Chong Qiu; Jigang Wang (Journal of Advanced Research)
Aging and aging-associated diseases (AAD), including neurodegenerative disease, cancer, cardiovascular diseases, and diabetes, are inevitable process. With the gradual improvement of life style, life expectancy is gradually extended. However, the extended lifespan has not reduced the incidence of disease, and most elderly people are in ill-health state in their later years. Hence, understanding aging and AAD are significant for reducing the burden of the elderly. Inorganic metal nanoparticles (IMNPs) predominantly include gold, silver, iron, zinc, titanium, thallium, platinum, cerium, copper NPs, which has been widely used to prevent and treat aging and AAD due to their superior properties (essential metal ions for human body, easily synthesis and modification, magnetism). Therefore, a systematic review of common morphological alternations of senescent cells, altered genes and signal pathways in aging and AAD, and biomedical applications of IMNPs in aging and AAD is crucial for the further research and development of IMNPs in aging and AAD. This review focus on the existing research on cellular senescence, aging and AAD, as well as the applications of IMNPs in aging and AAD in the past decade. This review aims to provide cutting-edge knowledge involved with aging and AAD, the application of IMNPs in aging and AAD to promote the biomedical application of IMNPs in aging and AAD.